x + 2 y + z = 5 ( x + y ) ( y...

Arraryeldergox2

Arraryeldergox2

Answered

2022-06-24

x + 2 y + z = 5 ( x + y ) ( y + z ) x + y + 2 z = 7 ( y + z ) ( z + x ) 2 x + y + z = 6 ( z + x ) ( x + y ) .
Find the value of 24 3 x y z.

Answer & Explanation

Kaydence Washington

Kaydence Washington

Expert

2022-06-25Added 32 answers

Assume x + y = a , y + z = b , z + x = c and express both LHS and RHS of all 3 equations in terms of a , b , c. After some simplification, you should be able to get a system of linear equations in 1 a , 1 b , 1 c .
Can you solve it now?

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?